Global Poverty and Hunger: Challenges and Strategies for Sustainable Human Development - MONCEA, Madalina Ioana; Dima, Cristina; PARCALABESCU, Razvan; CALIN, Ana-Maria (European Journal of Sustainable Development, 2025)
Poverty is a key aspect drawing the attention of macroeconomic analysis and global comparisons. To measure the extent of this phenomenon, a set of indicators is used to highlight, in a correlated manner, various qualitative and quantitative factors characterizing the evolution of poverty in a specific country or, more broadly, through comparative surveys at the international level. Although these indicators are not the only tools used in assessing social and economic development worldwide, they provide essential insights that enhance the relevance of such analyses. Ultimately, the very purpose of economic activity is to promote welfare and, as far as possible, to reduce—if not eradicate—poverty. This study presents both the theoretical framework and practical methods for calculating poverty, offering a synthesis of the indicators employed in its measurement. Keywords: development, globalization, hunger, poverty